Translation of the Koran in Europe - Курмaнбaев, К.; Есімқұлов, Е. Н. (Journal of Oriental Studies, 2017)
This article provides a brief overview of the history of the translation of the Koran into other languages, especially the most common European languages. Describes the influence of the Western position on the Quran from an academic point of view, but also takes into account the social, political and religious factors. Show translation analysis. Particular importance is attached to the Institute of Oriental Studies in the field of translation of the Koran.